Tachyplesin Causes Membrane Instability That Kills Multidrug-Resistant Bacteria by Inhibiting the 3-Ketoacyl Carrier Protein Reductase FabG - Liu, Cunbao; Qi, Jialong; Shan, Bin; Ma, Yanbing (Frontiers in Microbiology, 2018)
Tachyplesin is a type of cationic β-hairpin antimicrobial peptide discovered in horseshoe crab approximately thirty years ago that is well known for both its potential antimicrobial activities against multidrug-resistant bacteria and its cytotoxicity to mammalian cells. Though its physical interactions with artificial membranes have been well studied, details of its physiological mechanism of action the physiological consequences of its action remain limited. By using the DNA-binding fluorescent dye propidium iodide to monitor membrane integrity, confocal microscopy to assess the intracellular location of FITC-tagged tachyplesin, and RNA sequencing of the differentially expressed genes in four Gram-negative bacteria (Escherichia coli, Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa) treated with lethal or sublethal concentrations of tachyplesin, we found that compared with levofloxacin-treated bacteria, tachyplesin-treated bacteria showed significant effects on the pathways underlying unsaturated fatty acid biosynthesis. Notably, RNA levels of the conserved and essential 3-ketoacyl carrier protein reductase in this pathway (gene FabG) were elevated in all of the four bacteria after tachyplesin treatment. In vitro tests including surface plasmon resonance and enzyme activity assays showed that tachyplesin could bind and inhibit 3-ketoacyl carrier protein reductase, which was consistent with molecular docking prediction results. As unsaturated fatty acids are important for membrane fluidity, our results provided one possible mechanism to explain how tachyplesin kills bacteria and causes cytotoxicity by targeting membranes, which may be helpful for designing more specific and safer antibiotics based on the function of tachyplesin.